Utilization of natural and synthetic zeolitic materials as soil amendments in abandoned mine sites - Giannatou, Spyridoula; Vasilatos, Charalampos; Mitsis, Ioannis; Koukouzas, Nikolaos (Bulletin of the Geological Society of Greece, 2018)
The aim of this paper is to evaluate the effects of natural and synthetic zeolitic materials as soil amendments in contaminated soils. Two species of natural zeolites, clinoptilolite and mordenite, sampled from Samos Island, Greece, were used as low-cost modifiers (amendments). Both of these materials show perfect XRD-patterns. Moreover, coal fly ash (CFA) derived from the electrostatic precipitators of the Meliti power plant (Florina, Greece) converted via an alkaline hydrothermal treatment with 1M NaOH was used to produce a synthetic zeolitic material. The mineralogical composition of natural and synthetic zeolites was tested and identified by X-ray diffraction (XRD) and scanning electron microscope (SEM). The amendments and original contaminated soils from a former mining area of Lavrion, were mixed and equilibrated for 1 week, hydrated up to 40% of their water holding capacity. After the equilibration, the growth of Trifolium alexandrinum both in amended and original soils was studied in a pot experiment. The increase in pH value of treated soil by the tested amendments, confirmed the buffering effect and suggested the opportunity of using zeolitic materials for conditioning and remedying contaminated acidic soils from sulphidic mining areas. Moreover, the amended soils exhibited higher CEC values compared with unamended soil. Results showed that the synthetic zeolite produced by Meliti’s power station fly ash, was the most effective for plant growth, among the tested amendments. Between natural zeolitic materials from Samos Island, the most efficient was the clinoptilolite rich, probably because of its better water holding capacity compared with mordenite.